PENGGUNAAN ASYNCHRONOUS JAVASCRIPT AND XML (AJAX) PADA RANCANG BANGUN SISTEM E-LEARNING PENINGKATAN LITERASI SEJARAH DAN BUDAYA SULAWESI UTARA - Stevanus Kembuan; Kristofel Santa (LPPM Unbaja, 2025)
Indonesia ranks low in global literacy, with various surveys indicating a very low level of reading interest. To address this, the Ministry of Education and Culture launched the National Literacy Movement (GLN) in 2016, which includes cultural literacy aimed at preserving culture and promoting tolerance among the Indonesian people. However, the lack of educational materials on cultural literacy could threaten these positive achievements, particularly in North Sulawesi, a region with a high religious harmony index. As time progresses, it is hoped that existing technology can be utilized to provide solutions to human challenges, including improving human resources and promoting cultural and historical development. Therefore, this study aims to design an AJAX-based e-learning sistem focused on the history and culture of North Sulawesi, featuring interactive elements such as learning modules, quizzes, and discussion forums. The sistem will integrate technology with local culture to ensure that younger generations do not lose their national identity and cultural heritage, even in the middle of technological advancements.